A facile way to build up branched high functional polyaminoacids with tunable physicochemical and biological properties. (April 2016) - Mauro, Nicolò; Fiorica, Calogero; Varvarà, Paola; Di Prima, Giulia; Giammona, Gaetano
Graphical abstract: Highlights: New polyaminoacids endowed with predictable physicochemical properties is reported. The amount of amino acidic side chains can be kinetically tuned. Side basic residues leads to supramolecules exploitable as drug delivery systems. Abstract: Here, for the first time, branched polyaminoacids bearing α-amino acids as side functions, namely PAA-co-AA and PGA-co-AA, are prepared by heterophase ring opening of polysuccinimide (PSI) withl -arginine or glycine in aqueous environment and at controlled pH. The modulation of the pH of the reaction leads to high-molecular-weight copolymers with tunable functionalization and, as consequence, with tailor-made physicochemical properties. Furthermore, a branched polyaminoacid carrying a preformed bioactive peptide (l -trileucine) andl -arginine as side pendants, named PATA-co-AA, was synthesized via a similar pathway thus leading to complex biomimetic materials potentially exploitable in several biomedical fields. Acid-base titrations, circular dichroism studies and spectrofluorimetric analysis show that the physicochemical behavior of this class of bioinspired copolymers can be predicted considering the starting features of the selected building blocks, implying that a careful choice of functional amino acids or peptides provides good chance for obtaining macromolecule libraries with selected properties.